Crossing risky boundaries: Learning to authentically and equitably co-teach through design and practice. (November 2019) - Hackett, Jacob; Bang, Megan; Goulter, Arielle; Battista, Maritess
Highlights: Co-teaching should be viewed as an activity system, shifting from sets of practices, checklists or procedures. Activity systems consider co-teacher beliefs, psychological safety, instructional practices and practitioner learning. Participants sharpened their language and co-teaching practice by designing 2 novel and adaptable co-teaching tools. The Co-teaching Implementation Framework is a powerful initial step towards a nuanced theory of the co-teaching system.